Analysis of Work Posture in Rice Processing Unit to Reduce Risk of Musculoskeletal Disorders: A Case of Indonesia - Suryaningrat, Ida Bagus Bagus; Mahardika, Nidya Shara; Rusdianto, Andrew Setiawan; Endah Hapsari, Shinta Syafrina; Pratiwi, Annisa Ayu (International Journal on Food, Agriculture and Natural Resources, 2025)
This modern milling facility, called the Modern Rice Milling Plant (MRMP), operates in the field of logistics or warehousing and consists of seven production processes: raw material reception, drying process, storage (silo), milling, sorting, packaging, and stock handling. Musculoskeletal disorders (MSDs) are among the most common health problems directly associated with working conditions. This study aims to analyze workers' posture by evaluating working postures during the rice processing activities at MRMP Bulog in Jember Regency, to identify workers' Musculoskeletal Disorders (MSDs) complaints during the rice processing process at MRMP Bulog Jember, and to provide posture recommendations to reduce the risk of high-risk MSD-related injuries during rice processing activities at MRMP Bulog Jember. This research was conducted from April to June 2025. The sample consisted of 5 individuals from the raw material reception and rice transportation to the truck sections, which are part of the rice processing population. The final OWAS score at the raw material reception stage (P1 and P2) was 3, indicating that improvements must be made as soon as possible. Similarly, during the rice transportation to the distribution truck (P3, P4, and P5), the OWAS final score was also 3, meaning that improvements are urgently needed to prevent work-related accidents. Therefore, the current method and tools used during the raw material reception stage pose a high risk to workers' bodies, and immediate improvements are necessary. The recommended tool is a long, pointed iron rod used to pierce or unload wet paddy sacks. This tool is suggested to facilitate the workers in performing their tasks and to minimize the occurrence of accidents or Musculoskeletal Disorders (MSDs).